How freedom of movement infringes on the right to leave - Oelgemöller, Christina (Frontiers in Human Dynamics, 2023)
This article contributes to discussions that problematize the recent proliferation of soft law instruments in relation to international migration. The Global Compact for Migration has placed soft norm instruments more formally on the agenda of plausible tools with which to regulate people's movement. I am contributing to these discussions by engaging with the question of how the amalgamation of soft and hard law contributes to and impacts on legal effects, using a post-colonial feminist lens. I do so by focusing on the interaction between freedom of movement and the right to leave in the ECOWAS area, drawing on original research material collected mainly in Abuja, Nigeria but also in Senegal, Guinea and The Gambia. It is argued that freedom of movement provisions, as they are promoted by the ECOWAS and largely funded by inter-governmental organizations and European donor countries, end up infringing the right to leave. In a first step, existing norms at international, continental, regional and national level are discussed to prepare the ground to answer the question how such infringing is done. From this step I conclude that the triple layers of legal instruments, political instruments and programming are impairing the intent of the right to leave in the way that a politico-legal landscape is constructed within which programs operationalize freedom of movement. The next step then looks at freedom of movement programming at regional, national and local levels by asking about the subjectivities that are created -for example the 'potential migrant'; by shedding light on practices of resistance -for example in how national governments use diplomacy to disengage; and by highlighting how 'home patch' talk renders those potential migrants leaving not just implausible but suspect. It is found that, in the legal and political context of West Africa, soft norms thrive. The GCM constitutes an unhelpful list of random contradictory approaches that orient ideas, policy initiatives, programs, and ultimately people, towards being fixed in place, rather than being able to leave and to move freely should they want to. This happens in-country when people have not yet begun to move.